Bio-protection in oenology by Metschnikowia pulcherrima: from field results to scientific inquiry - Puyo, Maëlys; Simonin, Scott; Bach, Benoit; Klein, Géraldine; Alexandre, Hervé; Tourdot-Maréchal, Raphaëlle (Frontiers in Microbiology, 2023)
Finding alternatives to the use of chemical inputs to preserve the sanitary and organoleptic quality of food and beverages is essential to meet public health requirements and consumer preferences. In oenology, numerous manufacturers already offer a diverse range of bioprotection yeasts to protect must against microbiological alterations and therefore limit or eliminate sulphites during winemaking. Bio-protection involves selecting non-Saccharomyces yeasts belonging to different genera and species to induce negative interactions with indigenous microorganisms, thereby limiting their development and their impact on the matrix. Although the effectiveness of bio-protection in the winemaking industry has been reported in numerous journals, the underlying mechanisms are not yet well understood.The aim of this review is to examine the current state of the art of field trials and laboratory studies that demonstrate the effects of using yeasts for bio-protection, as well as the interaction mechanisms that may be responsible for these effects. It focuses on the yeast Metschnikowia pulcherrima, particularly recommended for the bio-protection of grape musts.